345 Comparable Safety Profile Between Laser Interstitial Thermal Therapy (LITT) and Stereotactic Needle Biopsy in 30-Day and 90-Day Readmission: A National Readmissions Database Analysis. (1st April 2022) - Alvi, Mohammed A.; Do, Truong; Howard, Madeleine; Huling, Jared; Palzer, Elise; Chen, Clark C.
Abstract : INTRODUCTION: The procedural elements of Laser Interstitial Thermal Therapy (LITT, also known as stereotactic laser ablation (SLA)) and stereotactic needle biopsy are highly similar. METHODS: We queried the National Readmission Database (NRD, 2010-18) for patients who underwent elective LITT or biopsy using International Classification of Diseases 9th and 10th edition codes. Readmission was defined planned, related admissions following the index admission. Odds of 30- and 90-days readmission were calculated using multivariable logistic regression. RESULTS: 305 LITT and 7, 419 needle biopsy treated brain tumor were identified. The LITT treated patients were younger (p < 0.001), female (p=0.008), and insured privately (compared to Medicare or Medicaid, p < 0.001). In terms of cancer type, a greater proportion of LITT cohort were patients brain metastasis (relative to primary brain cancer, 38.7% vs 7.2%, p < 0.001). There was no difference in non-routine discharge (LITT: 73.8%, n = 225 discharged to home vs biopsy: 80 %, n = 5, 392, p = 0.826) or in-hospital mortality (0.3%, n=1 vs 0.7%, n = 50, p = 0.715). The most common neurosurgical reasons for readmissions at 30-days included unplanned readmission for index diagnosis (LITT: 2%, n = 7 vs biopsy: 3.7%, n = 272), infection (0.6%, n = 2 vs 0.46%, n = 34), seizure (0.3%, n = 1 vs 0.74%, n = 54) and cerebrovascular complication (0.3%, n = 1 vs 1%, n = 55) . The most common reason for non-neurosurgical readmission at 30 days for biopsy treated patients was deep vein thrombosis (DVT) / pulmonary embolism (PE) (0.46%, n = 35) and for LITT treated patients was an electrolyte abnormality (0.6%, n = 2). In both univariate and multivariable analyses, the odds of 30- and 90-days overall readmission, as well as neurosurgical and non-neurosurgical readmission were comparable between LITT and biopsy. CONCLUSION: The NRD analysis of 30- and 90-day readmission suggest comparable safety profile between LITT and stereotactic needle biopsy as treatment for brain tumor patients.